Robust differential modulations for asynchronous cooperative systems - Cano, Alfonso; Morgado, Eduardo; Ramos, Javier; Caamaño, Antonio J. (Signal processing, 2014)
Accurate channel state information and time/frequency synchronization are challenging to acquire in mobile ad hoc cooperative set-ups, where resource-constrained relaying terminals rapidly (dis)join cooperation. This paper derives low-complexity differential modulations and cooperative transmission schemes so that detection at the receiver is feasible without channel knowledge or synchronization information. A simple distributed doubly-differential (DD) time-division multiplexing (TDM) scheme using diagonal space–time (ST) unitary codes is derived to bypass multiple carrier frequency offsets (CFOs) and collect space diversity. Precoded differential orthogonal frequency division multiplexing (OFDM) transmissions are derived to additionally bypass timing offsets and collect multipath diversity using either DD diagonal or single-differential (SD) orthogonal ST block codes (OSTBCs). DD diagonal mappings suffer from considerable coding gain and signal-to-noise ratio (SNR) loss due to unitary constellation constraints and noise enhancement at the receiver. SD-OSTBCs achieve higher performance with reduced decoding complexity, at the cost of reduced CFO mitigation range. Simple and robust non-coherent selective and adaptive transmissions are also included, showing that full space and multipath diversity can still be achieved even with decoding errors at relays. Simulations corroborate theoretical claims. •We develop a cooperative DD-TDM scheme that deals with multiple CFOs among relays.•We develop a DD-TDM OFDM scheme to allow for both CFO and timing/multipath effects.•We develop a SD-OSTBC OFDM scheme for high multipath spread and number of relays.•Simple and robust non-coherent selective and adaptive transmissions are also included.•Full space and multipath diversity are achieved even with decoding errors at relays.